2020
DOI: 10.1021/acsearthspacechem.0c00192
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Characterization of Urban Grime Sampled from Two Cities

Abstract: Urban grime can be an important substrate for heterogeneous reactions in cities. Studies performed using laboratory-prepared urban grime proxies and urban grime collected from the field indicate that the physicochemical properties of urban grime can greatly affect heterogeneous reaction rate constants. We investigated several properties of urban grime collected from two cities in the north-east region of the United States of America. Optical and Raman microscopy indicated that urban grime collected from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…46,47 The effect in UV wavelengths relevant to indoor photochemistry has not been quantified. Recently, our research group reported that urban grime absorbs solar radiation throughout the actinic region, 48 which suggests that UV irradiance indoors could be reduced at high urban grime surface coverages. However, the results also imply that urban grime surface coverage on windows will often be very low.…”
Section: Window Transmittance Of Direct Sunlightmentioning
confidence: 99%
“…46,47 The effect in UV wavelengths relevant to indoor photochemistry has not been quantified. Recently, our research group reported that urban grime absorbs solar radiation throughout the actinic region, 48 which suggests that UV irradiance indoors could be reduced at high urban grime surface coverages. However, the results also imply that urban grime surface coverage on windows will often be very low.…”
Section: Window Transmittance Of Direct Sunlightmentioning
confidence: 99%
“…Because film compositions are often dominated by particles, measuring changes to particulate morphology (e.g., sizes and shapes) can help us estimate a film's adsorptive capacity. 2,12 Outdoor film formation models have been reported, but pathways and the effects of film maturation are unknown or remain poorly defined. 11,14 Formation models generally suggest that (semi-)volatile organic molecules and particles first encounter a viscous sublayer surrounding solid objects, then cross this layer, and finally interact physically with the underlying surface material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16,17 In fact, the precursor film may only be a few nanometers thick, and recent studies have suggested that the majority of a film's ultimate mass comprised of super-micron-sized particles. 1,2,14 these studies, the organic portion of the film has been quantified at 10−40% of the film's total mass with 10% of that being monocarboxylic acids and 35% being aliphatic species. 17 The inorganic portion has been identified to be 60−90% of the total mass with ∼7% of this material being nitrates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations